Klinični pomen mutacije V617F JAK2 gena pri kroničnih mieloproliferativnih boleznih - prve izkušnje - Vučković, Joško (Zdravniški vestnik, 2006)
Background. An acquired V617F mutation in the JAK2 gene was found to occur in most patients with polycythaemia vera (PV) and about a half of those with essential thrombocythaemia (ET) and chronic idiopathic myelofibrosis (CIMF). It is the first chlonal marker that allows differentiation between reactive thrombocytosis and erythrocytosis from some chronic myeloproliferative disorders (CMPD) - ET, PV, and CIMF. It has been proposed that the JAK2 status could also divide ET patients in two distinct subgroups, with mutation positive one showing clinical and laboratory features of PV. Patients and methods. Allele-specific PCR for JAK2 mutation was done in 53 patients (35 ET, 12 PV, and 6 CIMF). In the group of ET patients, some chlinical and laboratory features of mutation positive and mutation negative subgroup were compared. Results. In general we founf V617F mutation in 12/12 (100 %) PV, in 15/35 (43 %) ET and in 2/6 (33 %) CIMF. Mutation positive ET patients had higher hemoglobin (Hb) level and lower platelet counts already at diagnosis. The Hb level had the tendency to increase (observation period 35 months) and 2 patients converted to overt PV. In mutation nedative patients the Hb level remained equal or even was slightly decreased after observation period (42 months). Up to now there is no statistical difference in leukocyte count, incidence of splenomegaly, antiproliferative drugs demand, or disease related complications. Platelet distribution width (PDW) was higher in mutation positive group. Conclusions. The fraction of V617F mutation positive patients with CMPD in our work is similar to that found by others. We found this test very useful in differentiation of some CMPD cases from the reactive states. Mutation positive ET shares some clinical and laboratory features with PV and overt polycythemic transformation in such patients is possible.
Keywords: diagnostika; geni; krvne bolezni; Mielofibroza; Mieloproliferativne bolezni; mutacije; Myelofibrosis; Myeloproliferative disorders; Policitemija, prava; Polycythemia vera; Thrombocytosis; Trombocitoza